Conjunctival cytology in glaucomatous patients using long-term topical therapy - Sherwani Rana; Khan Roobina; Pervez Mohd; Tauheed Asma; Ashraf H; Jilani F (Journal of Cytology, 2008)
Background: Long-term use of antiglaucoma drugs induces adverse changes on the conjunctival surface. Aim: To evaluate the cytological changes in the conjunctival scrape smears of patients receiving long-term antiglaucoma medication and their histopathological correlation. Materials and Methods: Conjunctival scrape smears were taken from the eyes of patients on long-term antiglaucoma therapy for over three months (n = 75), patients taking antiglaucoma medication for less than three months (n = 100) and from glaucomatous patients in whom trabeculectomy was done as a primary procedure. Inflammatory cell counts, fibroblasts, and the degree of metaplasia were then evaluated both cytologically and histologically. The t-test was used to determine the predictive values of these parameters for the surgical outcome of trabeculectomies. Results: Long-term use of antiglaucoma therapy leads to a higher stage of metaplasia with an increase in the number of fibroblasts, subepithelial collagen deposition, and inflammatory infiltrate within the substantia propria of the conjunctiva. Conclusions: Long-term antiglaucoma medications induce a significant degree of metaplasia in the conjunctival surface that adversely affects the outcome of filtration surgery.